Pharmacokinetic Drug-Drug Interaction and Responsible Mechanism between Memantine and Cimetidine - Young A. Choi; Im-Sook Song; Min-Koo Choi (MDPI AG, 2018)
A sensitive and simple chromatography-tandem mass spectrometry (LC-MS/MS) method was developed to evaluate memantine in rat plasma. Memantine and propranolol (internal standard) in rat plasma was extracted using a methanol precipitation method. The standard curve value was 0.2–1000 ng/mL and selectivity, linearity, inter-day and intra-day accuracy and precision were within acceptance criteria. Using this validated method, drug-drug interactions between memantine and cimetidine was measured following co-administration of memantine and cimetidine intravenously and orally. Plasma exposure of memantine was increased by 1.6- and 3.0-fold by co-medication with cimetidine intravenously and orally, respectively. It suggested that the drug interaction occurred during the gut absorption process, which was consistent with the results showing that the intestinal permeability of memantine in the presence of cimetidine was 3.2-fold greater than that of memantine alone. Inhibition of cimetidine on hepatic elimination of memantine rather than renal excretion was also attributed to the drug-drug interaction between memantine and cimetidine, which explained the decreased clearance of memantine by co-medication with cimetidine. In conclusion, the newly developed simple and sensitive LC-MS/MS analytical method was applied to investigate the pharmacokinetic drug-drug interactions of memantine. Plasma exposure of memantine by co-administration with cimetidine was increased because of its enhanced intestinal permeability and the decreased metabolic activity of memantine.